The Right of Pre-Emption and Sale and Purchase of Property Is an Important Need of Today’s Society (In the Light of Qur’an and Sunnah): حق شفعہ اور جائیداد کی خرید و فروخت موجودہ معاشرے کی اہم ضرورت (قرآن و سنت کی روشنی میں) - Fatima, Dr. Erum; Akhter, Dr. Naseem; Seema, Dr. (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021)
In view of Islamic teaching at the time of sale or purchase of property, the neighbour of the seller of the property can purchase the same property, according to his own wish, fulfilling the entire legal terms and conditions in relation to the purchase of property, this deed is termed a: “Pre-emption:. This act is apparently a constraint and worsening the situation, in faet, it is also consistent to the rest of commands of Islamic Shariah. The right of pre-emption is Potential and stralegy-based. In faet this right prevents another neighbour (the new buger) from this the misconduct of his neighbour. To sum up this right is duly defined as one of the significant and fundamental codes of Shariah, and highly regarded as one of the laws and rules of the country. This research work was aimed to discuss the selected topic in the present scenario in detail.